The Effect of Curcuma longa Extract on Interleukin 6, Procalcitonin, Microbial Count, and Histopathology of the Lungs in a Rat Model Infected with Streptococcus pneumoniae - Prasetyo, Yudhi; Reviono, Reviono; Hikmayani, Nur Hafidha; Adhiputri, Artrien; Setijadi, Ana Rima (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Streptococcus pneumoniae causes 95% of cases of community-acquired pneumonia (CAP). Interleukin 6, procalcitonin, microbial count, and lung histopathology can help in determining indicators of inflammatory processes and prognosis. Curcumin, which acts as an anti-inflammatory and anti-microbial, can be used as an adjunctive therapy in infectious diseases. Methods: This was a laboratory experimental study. A sample of 30 white rats (Rattus norvegicus) infected with Streptococcus pneumoniae was carried out in the experimental animal laboratory at the Faculty of Medicine, Universitas Sebelas Maret in November 2022 with incidental sampling. The control group received 1cc of aquadest, the first treatment group received 30 mg/200 g of curcuma longa extract, the second treatment group received 50 mg/200 g of Curcuma longa extract, the third treatment group received 30 mg/200 g of Curcuma longa extract and 30 mg/200 g of amoxicillin, and the fourth treatment group received 30 mg/200 g of amoxicillin. Interleukin 6 and procalcitonin were measured on the third and twelfth days after the rats were infected with Streptococcus pneumoniae. The microbial count and histopathology of the lungs were assessed after the twelfth day. Results: There was a significant difference (P<0.05) in the decrease in levels of interleukin 6, procalcitonin, and microbial count in the treatment group compared to the control group. There was no significant difference (P>0.05) in the improvement in the histopathology of the lungs in the treatment group compared to the control group. Conclusion: Curcuma longa extract can significantly reduce levels of interleukin 6, procalcitonin, and microbial count, but not significantly improve the histopathology of the lung.